Update on the management of Lennox-Gastaut syndrome with a focus on rufinamide - Carl E Stafstrom (Dove Medical Press, 2009)
Carl E StafstromSection of Pediatric Neurology, Departments of Neurology and Pediatrics, University of Wisconsin School of Medicine and Public Health, Madison, WI, USAObjective: This review summarizes the treatment of Lennox-Gastaut syndrome, an intractable epileptic encephalopathy of early childhood. In particular, the review focuses on rufinamide, a recently released anticonvulsant medication with reported effectiveness in this epilepsy syndrome.Methods: A systematic literature search (PubMed) was performed to review the existing literature pertaining to the treatment of Lennox-Gastaut syndrome as well as studies involving rufinamide as an anticonvulsant medication.Results: The published literature to date documents a beneficial effect of rufinamide on children over 4 years old with Lennox-Gastaut syndrome. Studies indicate a significant decrease in tonic and atonic seizure frequency as well as total seizure frequency compared to placebo-treated children. Rufinamide appears to be well tolerated and a safe medication, somnolence and vomiting being the most common side effects.Conclusions: Rufinamide is a promising adjunctive therapy for Lennox-Gastaut syndrome, an intractable childhood epilepsy. To ensure its optimal effectiveness, clinicians must be familiar with the medication’s clinical response profile and potential for adverse effects.Keywords: pediatric, epilepsy, epileptic encephalopathy, Lennox-Gastaut syndrome, rufinamide